Study of mixed-symmetry excitations in 96Ru via inelastic proton-scattering. (9th February 2015) - Hennig, A; Spieker, M; Werner, V; Ahn, T; Anagnostatou, V; Cooper, N; Derya, V; Elvers, M; Endres, J; Goddard, P; Heinz, A; Hughes, R O; et al.
Abstract: Mixed-symmetry states of octupole ( L = 3) and hexadecapole ( L = 4) character have been recently proposed in the N = 52 isotones 92 Zr and 94 Mo, based on strong M 1 transitions to the lowest-lying 3 − and 4 + states, respectively. In order to investigate similar excitations in the heaviest stable N = 52 isotone 96 Ru, two inelastic proton-scattering experiments have been performed at the Wright Nuclear Structure Laboratory (WNSL), Yale University, USA and the Institute for Nuclear Physics, University of Cologne, Germany. From the combined data of both experiments, absolute E 1, M 1, and E 2 transition strengths were extracted, allowing for the identification of candidates for MS octupole and hexadecapole states. The structure of the low-lying 4 + states is investigated by means of sdg -IBM-2 calculations.